The Effect of Mass Ratio on Phytoremediation of Nickel Contaminated Water - Taha , Maha; Abdulwahab Al-Baldawi, Israa; Sheikh Abdullah, Siti Rozaimah; Ismail, Nur ’Izzati; Shamran Jasim, Salwa (Al-Khwarizmi Engineering Journal, 2022)
Water pollution is one of the global challenges that the society must address in the 21st century aiming to improve the water quality, reduce human pollutants and ecosystem health impacts. In phytotoxicity test, the plant of Iresine herbstii was exposed to remove nickel from simulated wastewater using two different ratios (mass of plant to the mass of nickel) (,Rp/Ni) for 21 days with sub-surface batch system. During the exposure period, the removal of Ni concentrations (2, 5 and 10 mg/L) for two mass ratio (2,800 and 34,000) were (83.6%, 77.2%, 78.0%) and (86.8%, 97% and 95.6%), respectively. final result of the rate was found that the highest removal occurred, 97%, at a mass ratio of 34,000 and a nickel concentration of 5 mg/L. Metal accumulation mechanism of plants were examined using bioconcentration factor (BCF) and translocation factor (TF) of metals which indicated that I. herbstii is suitable for phytostabilization of Ni (BCF>1 and TF